The author in esthetic activity and the functional text (on the basis of V. Mikhaylov’s narrative (“The chronicle of the great jute”) - Ainabekova, Gulzhan; Bayanbayeva, Zhadyra; Joldasbekova, Bayan; Zhaksylykov, Aslan (Opción, 2018)
Author‘s esthetic activity in the belletristic literature affects all aspects of the textual sphererevealing and shading the author's discourse, setting the direction andtonality, interacting with conceptual domain of all architectonics creation. Thedocumentary narrative «The Chronicle of Great Jute» by V. Mikhaylov reveals thefeatures where vigorous author‘s esthetic activity and the directional author‘s discourseembedded in the cascade of functional texts. The analysis of the well-known workshows that functionally significant quotes, hidden intertexts, illustrations, documentsallusions, reminiscences, references to memoirs and retrospections play an importanrole in designing of the work‘s stratagem for the organization of a wide polylogue in ahistorical and political context.